Indonesia Vision 2045 : Toward Water Security - World Bank (World Bank, Washington, DC, 2021)
Vision 2045 aims to significantly transform Indonesia with the target of becoming one of the world’s top five economies by the time it reaches its centenary in 2045. But is this achievable without considering Indonesia’s Water Security? This study reflects on this question in detail, highlights potential challenges and quantifies the impact of water related threats – if left unaddressed – on GDP and overall socio-economic development. It further suggests targeted actions to move toward water security and shows windows of opportunities for sector reform underpinned by the ongoing revisions of the legal and regulatory framework following the promulgation of the 2019 Water Law and 2020 Omnibus Law.